Effects of High-Frequency Oscillatory Ventilation With Volume Guarantee During Surfactant Treatment in Extremely Low Gestational Age Newborns With Respiratory Distress Syndrome: An Observational Study - Tana, Milena; Paladini, Angela; Tirone, Chiara; Aurilia, Claudia; Lio, Alessandra; Bottoni, Anthea; Costa, Simonetta; Tiberi, Eloisa; Pastorino, Roberta; Vento, Giovanni (Frontiers in Pediatrics, 2022)
Objective: to evaluate the effect of volume guarantee (VG) combined with High-frequency oscillatory ventilation (HFOV) on respiratory and other physiological parameters immediately after lung recruitment and surfactant administration in HFOV elective ventilated Extremely Low Gestational Age Newborns (ELGAN) with respiratory distress syndrome (RDS). Design: Observational study. Setting: Tertiary neonatal intensive care unit. Patients: Twenty-two ELGANs of 25.5 ± 1.1 weeks of gestational age requiring invasive mechanical ventilation and surfactant administration for RDS during the first 6 hours of life. Interventions: All infants intubated in delivery room, were managed with elective HFOV and received surfactant after a lung recruitment manoeuver. Eleven infants received HFOV + VG and were compared with a control group of 11 infants receiving HFOV alone. HFOV was delivered in both groups by Dräger Babylog VN500 ventilator (Dräger, Lubeck, Germany). Main outcome measures: Variations and fluctuations of delivered high-frequency tidal volume (VThf), fluctuation of pressure pressure amplitude (Delta P) and partial pressure of CO2 (pCO2) levels after recruitment manoeuver and immediately after surfactant administration, in HFOV + VG vs HFOV ventilated infants. Results: There were no significant differences in the two groups at starting ventilation with or without VG. The mean applied VThf per kg was 1.7 ± 0.3 mL/kg in the HFOV group and 1.7 ± 0.1 mL/kg in the HFOV+VG group. Thirty minutes after surfactant administration, HFOV group had a significant higher VThf/Kg than HFOV+VG, (2.1 ± 0.3 mL/kg vs 1.6 ± 0.1 mL/kg, p: <0.0001) with significantly lower pCO2 levels (43.1 ± 3.8 mmHg vs 46.8 ± 1.5 mmHg, p= 0.01), 54.4% of patients having pCO2 below 45 mmHg. Measured post-surfactant ∆P values were higher in HFOV group (17 ± 3 cmH2O than in HFOV + VG group (13 ± 3 cmH2O, p= 0.01). Conclusion: HFOV + VG maintains pCO2 levels within target range and reduces VThf delivered variations more consistently than HFOV alone after surfactant administration.